Morphological and Functional Evaluation of Chicken Blood Leukocytes in Chronic Ochratoxicosis - Janaczyk, Bartlomiej; Pliszczak-Krol, Aleksandra; Graczyk, Stanislaw; Houszka, Marek; Rouibah, Kamal (International Journal of Poultry Science, 2006)
The effects of ochratoxin A (OA) administration on the function and morphology of chicken blood leukocytes was evaluated. Two-weeks-old, broilers chickens (Cobb-500) were randomly divided into three groups, six birds each. The birds form the group I received a fodder without ochratoxin. The chickens from the group II were fed with fodder containing 6ppm of ochratoxin A for 10 days, while administration of ochratoxin to the birds from group III was prolonged up to 20 days. After 10 days of administration the OA containing fodder, there was recorded the increase of hematocrit (PCV) and characteristic for stress, decrease of lymphocyte percentage with simultaneous increase of heterophils percentage. The prolonged administration of the OA containing fodder to the subsequent 10 days, lead to the withdraw of the mentioned leukogram changes, decrease of PCV value and decrease of hemoglobin (Hb) level. Simultaneously, there was demonstrated that the heterophils of the chickens receiving OA, characterized with increased phagocytosis ability of the yeast cells (17% of phagocytizing cells in the group I, while in group II and III 26 and 37% respectively). However, the lymphocytes of these birds, after their incubation with oxalates mixture, characterized with decreased ability of radial segmentation of their nuclei (11.4% in the group I, 8% in the group III). The obtained results show not only OA immunosuppressive activity mechanisms, but also indicate the dissimilar or even very different sensitiveness of the particular leucocytes.